اسلامی معاشی نظام میں عدم استحکام اور تحقیقات امام احمد رضا خان:عصری و تحقیقی جائزہ: Instability in the Islamic Economic System and Research of Imam Ahmad Raza Khan's Contemporary and Research Review - Hafiz Muhammad Aqib Bilal,; Hafiz Muhammad Kashif,; Muhammad Wasi-ul-Akhlaq, (Al Manhal Research Journal, 2024)
The passage discusses the concept of an Islamic society, emphasizing that it is a structured and composed society designed according to the purpose for which humans were created. The implementation and fulfillment of this purpose are considered essential for the social and economic aspects of such a society, with its principles and regulations derived from the creator. The Quran is highlighted as the guiding source for the principles and regulations, emphasizing obedience to Allah and the Prophet. The economic policy proposed by Imam Ahmed Raza Khan is mentioned as a means to achieve economic stability in Islamic society, suggesting the formation of a committee to implement these principles for the development and well-being of Pakistan's Islamic society and addressing issues related to Kashmir and Palestine at the government level.